Research handbook on transnational corporations - De Jonge, Alice; Tomasic, Roman (Research handbooks on globalisation and the law, 2017)
Transnational corporations (TNCs) have moved to the forefront of regulatory governance both within states and in the international arena. The Research Handbook on Transnational Corporations provides expert background commentary and up-to-date insights into regulatory frameworks impacting on TNCs at global, industry and national levels. Written by global experts in their field, this unique collection of essays provides in-depth understanding of how the forces of globalisation affect the world's largest corporations, and how those corporations, in turn, shape globalisation. Comprehensive yet highly accessible, this is the first major work on the reciprocal impact of TNCs on regulatory processes. The Research Handbook provides guidance on how best to understand the rapidly evolving relationship between TNCs and the processes of treaty making, the formation of global industry standards and the processes of national law making and policy formation (with a focus on resource taxation). Global, industry and national-level case studies are used to explain the basic principles used to support state, private, and international regulatory programs. Delivering both theoretical and practical insights into the regulation of TNCs, this timely and authoritative Research Handbook will be of particular interest to policy makers, industry practitioners and lawyers. Students and academics will also find it to be an invaluable resource.